Examination of the relationship between Sustainable Competitive Advantage and Strategic Leadership in the Computer Industry: based on the evaluation and analysis of Dell and HP - Guan, Yueyao (2008)
Abstract Based on the evaluation and analysis of two predominate companiesÃÂ¢ÃÂÃÂ performances, Hewlett-Packard and Dell Inc, in the computer industry. This paper has found that a right strategic move at the right time is crucial but only makes half of the story. In order to achieve long-term successes, strategic leaders must make sure the compatibility between the corporate strategy and the competitive advantage exists before a major strategic change is made.